Assessing cosmetic results after breast conserving surgery. Issue 1 (13th March 2014) - Cardoso, Maria João; Oliveira, Helder; Cardoso, Jaime; Rubio, Isabel T.; Dixon, J. Michael
Abstract "Taking less treating better" has been one of the major improvements of breast cancer surgery in the last four decades. The application of this principle translates into equivalent survival of breast cancer conserving treatment (BCT) when compared to mastectomy, with a better cosmetic outcome. While it is relatively easy to evaluate the oncological results of BCT, the cosmetic outcome is more difficult to measure due to the lack of an effective and consensual procedure. The assessment of cosmetic outcome has been mainly subjective, undertaken by a panel of expert observers or/and by patient self‐assessment. Unfortunately, the reproducibility of these methods is low. Objective methods have higher values of reproducibility but still lack the inclusion of several features considered by specialists in BCT to be fundamental for cosmetic outcome. The recent addition of volume information obtained with 3D images seems promising. Until now, unfortunately, no method is considered to be the standard of care. This paper revises the history of cosmetic evaluation and guides us into the future aiming at a method that can easily be used and accepted by all, caregivers and caretakers, allowing not only the comparison of results but the improvement of performance. J. Surg. Oncol. 2014 110:37–44. © 2014 Wiley Periodicals, Inc.